Structure and electrical properties of Laₒ.₆₇Caₒ.₃₃ (Mn₁₋ₓCuₓ)O₃ perovskite - Lim, Kean Pah; Shaari, Abdul Halim; Talib, Zainal Abidin; Yahya, Noorhana; Lee, O. J.; Foon, J. V. (Universiti Putra Malaysia Press, 2005)
Manganese oxides of La0.67Ca0.33(Mn1-xCux)O3 (LCMCO) with x=0.00, 0.05 and 0.10 were prepared using solid-state reaction technique. Atomic Force Microscope (AFM) micrograph shown that the grain size increase from 2μm to 4μm when Cu is introduced. From the XRD analysis, the structure of all the samples shows a singlephase perovskite structure with the presence of minor impurities. The system exhibit an orthorhombic distorted perovskite structure, which resulted from the Jahn-Teller distortion. Mel-insulator transition temperature, Tp was observed from the temperature dependence of resistance curves. A broad Metal-Insulator transition is observed for samples x=0.00 and 0.05 except for x=0.10 which show a sharp transition at Tp. This might suggested that small doping concentration strongly influence to its magnetic properties. At highest doping concentration x=0.1, it might lead to direct paramagnetic to antiferromagnetic transition. The measurement of the magnetic field dependence of CMR was measured from 0T to0.9T. Overall, all sample did not show any saturation behavior when magnetic field up to 0.9T is applied. Therefore, higher CMR value can be achieved if stronger field is applied and high field is needed to saturate the magnetic ordering in these samples. The highest CMR value that is obtained in this work is 45% for sample drop with x=0.10 measured at 200K.